Trauma-related emotions and radical acceptance in dialectical behavior therapy for posttraumatic stress disorder after childhood sexual abuse - Görg, Nora Saskia; Priebe, Kathlen; Böhnke, Jan R.; Steil, Regina; Dyer, Anne; Kleindienst, Nikolaus (Borderline Personality Disorder and Emotion Dysregulation, 2017)
Background: Posttraumatic Stress Disorder (PTSD) related to childhood sexual abuse (CSA) is often associated with a wide range of trauma-related aversive emotions such as fear, disgust, sadness, shame, guilt, and anger. Intense experience of aversive emotions in particular has been linked to higher psychopathology in trauma survivors. Most established psychosocial treatments aim to reduce avoidance of trauma-related memories and associated emotions. Interventions based on Dialectical Behavior Therapy (DBT) also foster radical acceptance of the traumatic event. Methods: This study compares individual ratings of trauma-related emotions and radical acceptance between the start and the end of DBT for PTSD (DBT-PTSD) related to CSA. We expected a decrease in trauma-related emotions and an increase in acceptance. In addition, we tested whether therapy response according to the Clinician Administered PTSD-Scale (CAPS) for the DSM-IV was associated with changes in trauma-related emotions and acceptance. The data was collected within a randomized controlled trial testing the efficacy of DBT-PTSD, and a subsample of 23 women was included in this secondary data analysis. Results: In a multilevel model, shame, guilt, disgust, distress, and fear decreased significantly from the start to the end of the therapy whereas radical acceptance increased. Therapy response measured with the CAPS was associated with change in trauma-related emotions. Conclusions: Trauma-related emotions and radical acceptance showed significant changes from the start to the end of DBT-PTSD. Future studies with larger sample sizes and control group designs are needed to test whether these changes are due to the treatment. Trial registration: ClinicalTrials.gov, number NCT00481000.
Gesehen am 05.04.2018